Using statistical data in sexual harassment education through PBL in statistics - Syarifuddin Syarifuddin; Amanat Solikah; Ekita Rusdiyanti (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
The increasing prevalence of sexual harassment cases within educational settings underscored the urgency of integrating social issues into the learning process. This study examined the effect of implementing a Problem-Based Learning (PBL) model based on sexual harassment case data on students’ understanding of statistical concepts and data processing skills. A pre-experimental research design with a one-group pretest–posttest model was employed. The sample consisted of 100 fifth-grade students from Muhammadiyah 18 Elementary School in Surabaya, selected through purposive sampling. The research instrument was a statistical concept comprehension test, and the data were analyzed using a paired sample t-test. The analysis results showed a correlation coefficient of 0.662 with a significant value of p < 0.001, indicating that the implementation of the PBL model significantly improved students’ conceptual understanding. The effect size (Cohen’s d = 0.97) indicated a large practical impact of the intervention. These findings suggest that embedding real social issues into mathematics and statistics instruction can simultaneously strengthen cognitive skills and foster social awareness among students. However, as this study employed a one-group pretest–posttest design, further research with control groups is recommended to strengthen generalisability